Pendampingan Manajemen Keuangan Melalui Program Literasi Keuangan Kepada Komunitas Usaha Mikro Kecil dan Menengah (UMKM) yang Terjerat Rentenir di Kabupaten Nganjuk - Ainna Amalia FN; Lilis Rahmawati (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2019)
The development of UMKM in the process does not always go smoothly, sometimes the business also has obstacles, including being entangled by moneylenders. Therefore, the Assistant Team of Al ‘Ula Islamic Financial Institution of STAI Miftahul Ula Nglawak partnered with the NU LKK Nganjuk and Cooperative-UMKM Office of Nganjuk provides capital assistance without interest for MSME community through literacy programs. By using the Asset-Based Community Development (ABCD) method, this study aims to provide financial management assistance for UMKM Community who were entangeled by moneylenders. The results of the study indicate social change as follows: (1) awareness increases the productivity and work ethic; (2) the emergence of financial management skills through financial literacy; (3) financial literacy, which is the emergence of financial inclusion, financial passport, and financial access issues; (4) the emergence of efforts optimization to empower financial management capabilities; (5) able to make strategic planning to improve the level of the business community; (6) the emergence of new assistants; (7) there is a partnership between the assistant team and stakeholders.